2013
DOI: 10.1093/hmg/ddt610
|View full text |Cite
|
Sign up to set email alerts
|

CHD7 interacts with BMP R-SMADs to epigenetically regulate cardiogenesis in mice

Abstract: Haploinsufficiency for CHD7, an ATP-dependent nucleosome remodeling factor, is the leading cause of CHARGE syndrome. While congenital heart defects (CHDs) are major clinical features of CHARGE syndrome, affecting >75% of patients, it remains unclear whether CHD7 can directly regulate cardiogenic genes in embryos. Our complementary yeast two-hybrid and biochemical assays reveal that CHD7 is a novel interaction partner of canonical BMP signaling pathway nuclear mediators, SMAD1/5/8, in the embryonic heart. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 52 publications
1
40
0
Order By: Relevance
“…CHD7-containing complexes have been characterized in a variety of cell types, including human ESCs (PBAF), HeLa cells (WDR4, FAM124B), mouse neural progenitors (SOX2 and other proteins), and cardiomyocytes (SMAD1/5/8 and Brg1) (29,32,(39)(40)(41)(42). The lack of interaction between CHD7 and RA suggests that instead of functioning in the same large complex, CHD7 may regulate nucleosome accessibility independent of RAR/RXR heterodimers.…”
Section: Discussionmentioning
confidence: 99%
“…CHD7-containing complexes have been characterized in a variety of cell types, including human ESCs (PBAF), HeLa cells (WDR4, FAM124B), mouse neural progenitors (SOX2 and other proteins), and cardiomyocytes (SMAD1/5/8 and Brg1) (29,32,(39)(40)(41)(42). The lack of interaction between CHD7 and RA suggests that instead of functioning in the same large complex, CHD7 may regulate nucleosome accessibility independent of RAR/RXR heterodimers.…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, the FOG2-NuRD interaction inhibits the cell cycle inhibitor gene Cdkn1a to maintain cardiomyocyte proliferation in the myocardium; the FOG2-NuRD disruption phenotype can, thus, be rescued via ablation of Cdkn1a. CHD7, by contrast, transcriptionally regulates multiple processes during heart development and Chd7 mutants, as mentioned above, recapitulate the cardiac aspects of CHARGE syndrome (Liu et al, 2014;Payne et al, 2015) and mutations in CHD7 are found in sporadic cases of human congenital heart defects (Zaidi et al, 2013).…”
Section: Developmental Roles Of Chd Complexesmentioning
confidence: 95%
“…In developing neural crest cells, CHD7 interacts with members of the PBAF complex to regulate expression of Twist, Slug, Snail, and Sox9 and with Brg1 specifically to promote PlexinA2 expression [37,40]. Cardiac myocytes, some of which are likely to have their developmental origins in neural crest, also express CHD7 and form complexes with R-SMAD proteins SMAD1/5/8, (components of the BMP signaling pathway) which then regulate expression of the cardiac transcription factor gene Nkx2.5 [41]. These examples illustrate the variety of protein complexes and cell types/tissues involved in CHD7 functions.…”
Section: Introductionmentioning
confidence: 99%